In vitro antibacterial activity of Q-35, a new fluoroquinolone. - Ito, T (1992)
The in vitro activity of Q-35, an 8-methoxy fluoroquinolone, was compared with those of ofloxacin, ciprofloxacin, tosufloxacin, lomefloxacin, and sparfloxacin. The MICs of Q-35 for 90% of strains tested (MIC90s) of Staphylococcus aureus, methicillin-resistant S. aureus, Staphylococcus epidermidis, Streptococcus pneumoniae, and Streptococcus pyogenes were 0.2, 6.25, 0.2, 0.39, and 0.39 micrograms/ml, respectively. The activity of Q-35 was 4- to 16-fold greater than those of ofloxacin, ciprofloxacin and lomefloxacin but equal to those of tosufloxacin and sparfloxacin against these organisms. For 82 ciprofloxacin-resistant staphylococci (MIC90 = 100 micrograms/ml), Q-35 was the most active of the new quinolones tested (MIC90 = 6.25 micrograms/ml). The MIC90s of Q-35 against Escherichia coli, Enterobacter aerogenes, and Pseudomonas aeruginosa were 0.2, 0.78, and 12.5 micrograms/ml, respectively, and Q-35 was 2- to 16-fold less active than the other quinolones tested. Q-35 showed potent bactericidal activity and inhibited the supercoiling activity of DNA gyrase of S. aureus, E. coli, and P. aeruginosa.